Application of system dynamics approach in scale evolution of electric vehicles for education. Issue 2 (April 2021) - Yang, Xinran; Xiang, Yue; Lv, Lin; Liu, Junyong
Due to the increasing realisation of improving the utility of energy and reducing pollutant emissions, the electric vehicle has been a hot topic in electrical engineering courses. However, it is the scale evolution of electric vehicles that is the basis for investigating their impacts on the power grid. This paper presents the main steps of designing an educational tool based on system dynamic approach to understanding the electric vehicles evolution and arouses their interests in the course named Electric Vehicle and Smart Grid . This tool is a work done by a team of students based on theory and survey, calculating the size of electric vehicles. The effectiveness of this tool is verified by the case studies in this paper, including the scale evolution, analysing the influence factors and stimulating students' interests. In addition, this tool has been used in teaching to demonstrate the scale evolution intuitively, thus achieving better teaching.